2013
DOI: 10.1111/jpm.12038
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported depressive symptoms in women hospitalized for acute coronary syndrome

Abstract: The purpose of this cross-sectional observational study was to explore depressive symptoms, among 377 women, during hospitalization for acute coronary syndrome (ACS). Women were screened for depressive symptoms using the Beck Depression Inventory-II (BDI-II). Pearson chi-square tests for independence were used for comparisons between categorical variables and t tests for independent samples were used for comparisons between continuous variables. Tukey’s HSD test along with one-way ANOVA test was used to conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Researchers in Thailand, however, showed that men are more likely to develop psychological disorders after a stroke, but age was not a predisposing factor [13]. The experience of these symptoms, as well as the severity among women may be constant at all stages of life [14].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in Thailand, however, showed that men are more likely to develop psychological disorders after a stroke, but age was not a predisposing factor [13]. The experience of these symptoms, as well as the severity among women may be constant at all stages of life [14].…”
Section: Discussionmentioning
confidence: 99%